2018
DOI: 10.12816/0044058
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Tympanic Membrane Perforation in Tertiary Health Institution

Abstract: Background: Traumatic tympanic membrane perforation is a common otologic disorder with associated hearing impairment. Objective: This study aimed at determining the clinico-epidemiological pattern, etiological factors, clinical presentation and management of traumatic tympanic membrane perforation in a Tertiary institution in Nigeria. Materials and Methods: This was a prospective hospital based study of patients with history of traumatic perforated of tympanic membrane. The study was carried out over a period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 12 publications
4
10
0
10
Order By: Relevance
“…The remarkable complications seen in the foreign bodies in the ear in this study were bleeding, traumatic perforated tympanic membrane and hearing impairment. Similarly, these complications were observed in another study [24]. These complications arose from the foreign body or the attempted efforts to remove it.…”
Section: Fig 2 Sources Of Referral Of the Patientssupporting
confidence: 52%
“…The remarkable complications seen in the foreign bodies in the ear in this study were bleeding, traumatic perforated tympanic membrane and hearing impairment. Similarly, these complications were observed in another study [24]. These complications arose from the foreign body or the attempted efforts to remove it.…”
Section: Fig 2 Sources Of Referral Of the Patientssupporting
confidence: 52%
“…10 Our observation is also in accordance with study of Adegbiji from Nigeria, revealed that conductive hearing loss was the most common type of hearing impairment accounted for 326(61.6%), followed by sensorineural hearing loss 134(25.3%), while the common degree of hearing impairment was mild to moderate degree of hearing loss that accounted for 249(47.1%). 15 In present study spontaneous healing took place in 97 patients (85.1%), however amongst surgical procedures overlay myringoplasty was commonest (7, 6.1%) in those where perforation persisted beyond six months, which is keeping with Wani's work where overall spontaneous healing was achieved in 91.1% patients, and tympanoplasty was performed in 8(2.3%) patients. 17 According to available literature spontaneous healing of TTMP occurs in 80 -100% cases.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, Adegbiji and colleagues from Nigeria conducted a study in 2018 and their observations were that left ear was involved more than right (43.9%, 232), grade 1(small size) perforation was most common (39.3%, n-208) and central part of membrane was predominantly affected (38.2%, n-202). 15 These results are also supported by studies of Sogebi and Wani. 16,17 The left ear predominance can be explained as during interpersonal assault left is more close to assaulter.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In this study, it was found that most CSOM patients complained of otorrhea which was similar to a previous study that 19.6% of CSOM patients complained of otorrhea [ 3 ]. Otorrhea is the most common symtomp complain by CSOM patients caused by a long-lasting inflammatory process in the middle ear increasing proinflammatory cytokines such as TNF-α and IL-8 causes mucus cell metaplasia/hyperplasia resulting in increased secretion of fluid in the middle ear [ 26 , 27 ]. A study by Singh et all found 25% of CSOM patients had subtotal tympanic membrane perforation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%